(untitled) (Czech Journal of International Relations, 1967)
I will try to give a partial overview, writing a kind of vision of Western writers for the doctrine that concerns Czechoslovakia after the Second World War. Even if this production today falls more into the field of historiography, it concerns 1 interpretation, the international position of Czechoslovakia by taking into account the questions of the Czech-Soviet alliance, but it is also a document of how the fallen development of this state was deeply inscribed in general history, to the history of world politics. I think it will be beneficial to review the sources from which anti-Czechoslovak propaganda, or simply journalism about Czechoslovakia, still draws its inspiration today. And that is precisely because next year will give an opportunity for different reflections on the twentieth anniversary of the events of February 1 and the fiftieth anniversary of the establishment of the Czechoslovak Republic.